2018
DOI: 10.1002/jhet.3105
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐assisted Synthesis of Novel Pyrazole and Pyrimidine Derivatives as Antimicrobial Agents

Abstract: Herein, we report a convenient and facile methodology for the synthesis of new series of pyrazole and pyrimidine derivatives 2a–f and 3a–f under ultrasound irradiation. Pyrazole and pyrimidine derivatives have been synthesized in better yields and shorter reaction times compared with the conventional method. The chemical structures of all the synthesized compounds were elucidated by their IR, 1H NMR, 13C NMR, MS, and elemental analysis. Further, the target compounds were screened for their antimicrobial activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…[13] Azoles are one of the important classes of five-membered nitrogen-containing heterocycles. [14][15][16][17][18][19][20][21] The nitrogen-containing azoles have an important effect on structural modifications and biological interactions because of the advantage of two nitrogen heteroatoms in the ring. There are different types of azoles such as imidazole, triazole, tetrazole, and pentazole.…”
Section: Introductionmentioning
confidence: 99%
“…[13] Azoles are one of the important classes of five-membered nitrogen-containing heterocycles. [14][15][16][17][18][19][20][21] The nitrogen-containing azoles have an important effect on structural modifications and biological interactions because of the advantage of two nitrogen heteroatoms in the ring. There are different types of azoles such as imidazole, triazole, tetrazole, and pentazole.…”
Section: Introductionmentioning
confidence: 99%
“…The pyrimidine moiety is an essential part of RNA and DNA, providing various biological properties such as potent fungicide and bactericide . Some pyrimidine analogues are also known to acquire anticancer, antimalarial, antiviral, antibacterial, , antifungal, , anticonvulsant, and antihistamine activities. Certain 3,4-dihydropyrimidines have developed as essential props of numerous calcium antihypertensive agents, adrenergic, channel blockers, and neuropeptide antagonists .…”
Section: Introductionmentioning
confidence: 99%
“…In the continuation of our previous work [11][12][13][14][15][16][17][18][19][20][21][22][23] , it was confirmed that until now none of the methods had used such a mild and green catalyst and solvents for Dakin oxidation. The designed method is suitable for the conversion of substituted benzaldehydes to its consequent substituted phenols.…”
Section: Introductionmentioning
confidence: 73%